The Reparative Work of the Imagination: Yemen, 'Afiya, and the Politics of the Umma (American Journal of Islam and Society, 2024)
This paper explores the psychic implications of nation-state politics on Yemenis and the necessity of repair and restorative justice. It examines some burgeoning work by artists and filmmakers that work on the image of the Yemeni as a reaction to the mental health crisis, ongoing war, and dispossession. For many of my interlocutors, the exploration and reimagining of Yemeni history, identity, and their place within a larger umma beyond nation-state formation becomes a necessary act of repair—and a precondition toward broader political aspirations. The essay traces the works of art by two Yemeni artists that meditate on the conditions of community, trust, and individual and communal wellbeing in relation to the Muslim umma. In turn, it considers how an ummatic aspiration is mediated by local political histories, but also the difficult psychic work necessary to articulate this aspiration amid cultural desolation.